A new product on 2 × 2 matrices. (August 2020) - Kramer, Linus; Kramer, Peter; Man'ko, Vladimir
Abstract: We study a bilinear multiplication rule on 2 × 2 matrices which is intermediate between the ordinary matrix product and the Hadamard matrix product, and we relate this to the hyperbolic motion group of the plane.